An interface shell element for coupling non-matching quadrilateral shell meshes. (1st October 2018) - Ho-Nguyen-Tan, Thuan; Kim, Hyun-Gyu
Highlights: Interface shell elements can be easily defined to couple non-matching quadrilateral shell meshes. Shape functions for interface shell elements are explicitly presented in a polynomial form. The MITC approach is successfully employed to avoid the transverse shear locking of interface shell elements. An assumed membrane strain field is used to alleviate the membrane locking in curved interface shell elements. Interface shell elements can successfully alleviate locking phenomena and show good convergence for non-matching mesh problems. Abstract: In this study, a novel interface shell element (ISE) is developed based on a variable-node element formulation to couple non-matching quadrilateral shell meshes. Shape functions for ISEs are explicitly presented in a polynomial form with the use of appropriate supports of weight functions in moving least square (MLS) approximation. Assumed natural strains in the form of the mixed interpolation of tensorial components (MITC) approach are employed to avoid the transverse shear locking when the thickness of shell tends to zero. Moreover, an assumed membrane strain field defined over quadrilateral subdomains subdividing an ISE is used to alleviate the membrane locking in curved ISEs. Numerical experiments show the effectiveness and efficiency of ISE for connecting dissimilar quadrilateral shell meshes at a common interface.